The Strategy to Build Educative Interaction in Islamic Education on Online Learning Setting - Rony Sandra Yofa Zebua (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2020)
Nowadays, online learning has forced educational stakeholders to sufficiently involve online learning by handling the fundamental difference from traditional learning platforms. While educative interaction is vital but very limited to online learning, the teachers should condition the new environment to enable the learning process. However, educative interaction on online learning requires exact syntax to help the teachers implement it correctly. Therefore, this study aimed to identify the implementation of educative learning on online learning and formulate the syntax to help teachers create educative interaction. The study focused on Islamic and Character Education subjects. The research method is qualitative, using in-depth interviews to gather the data. The informants were from 2 different elementary schools. The study result revealed two types of syntax for educative interaction on online learning: the syntax of educative interaction on real-time chatting app and syntax of educative interaction on the video conference app. Every syntax has similar general phases: preparation, introduction, core, and closing. However, every phase has different details, adjusted to the service provided by the application used. Eventually, the teachers' competence and spirit and supporting infrastructure become the primary factors in maximizing the interaction. Besides, application choice determines the strategy that will be done.